2015
DOI: 10.1152/jn.00431.2015
|View full text |Cite
|
Sign up to set email alerts
|

Spatial phase sensitivity of complex cells in primary visual cortex depends on stimulus contrast

Abstract: [3457][3458][3459][3460][3461][3462][3463][3464][3465][3466][3467][3468][3469][3470] 2010). However, drifting gratings confound the influence of spatial and temporal summation, so here we have stimulated complex cells with gratings that are spatially stationary but continuously reverse the polarity of the contrast over time (contrastreversing gratings). By varying the spatial phase and contrast of the gratings we aimed to establish whether the contrast-dependent phase sensitivity of complex cells results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Previous work has demonstrated that the classification of simple cells does not vary with contrast in the cat and primate (cat: Crowder et al, 2007; van Kleef et al, 2010; monkey: Henry and Hawken, 2013; Cloherty and Ibbotson, 2015; Meffin et al, 2015). We first examined whether this is also true in mouse V1 by measuring the changes in the modulation ratios for spiking rate (F 1 /F 0 ) and membrane potential (V 1 /V 0 ) of individual simple cells with contrast (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated that the classification of simple cells does not vary with contrast in the cat and primate (cat: Crowder et al, 2007; van Kleef et al, 2010; monkey: Henry and Hawken, 2013; Cloherty and Ibbotson, 2015; Meffin et al, 2015). We first examined whether this is also true in mouse V1 by measuring the changes in the modulation ratios for spiking rate (F 1 /F 0 ) and membrane potential (V 1 /V 0 ) of individual simple cells with contrast (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While this difference between cell classes is clear when the stimulus strength is high, reducing stimulus strength diminishes the differences between the cell types. In particular, low contrast gratings evoke modulated responses in many complex cells (cat: Crowder et al, 2007; van Kleef et al, 2010; monkey: Henry and Hawken, 2013; Cloherty and Ibbotson, 2015; Meffin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The classifications based on these two methods often agree with one another (Dean and Tolhurst 1983;De Valois et al 1982a;Henry and Hawken 2013;Mata and Ringach 2005;Sengpiel et al 1997), but the agreement is not always complete (see Chen et al 2009;Skottun et al 1991 for reviews). Also, there are always some neurons whose behaviors fall between the "pure" types defined by either method (Crowder et al 2007;Hietanen et al 2013;Kagan et al 2002;Mata and Ringach 2005;Meffin et al 2015;Van Kleef et al 2010). Note that some recent physiological studies (Chance et al 1999Martinez and Alonso 2003;Priebe et al 2004; see also Mechler and Ringach 2002 for a review) have suggested that the simple and complex cells are better conceptualized as end points of a continuum rather than as a categorical distinction.…”
Section: Discussionmentioning
confidence: 99%
“…Most simple cells respond strongly to 8 oriented edges or gratings with a preference for a particular orientation (grating stimuli 9 consist of spatially periodic light and dark bands at a given orientation). 10 In contrast, complex cells exhibit significant nonlinear spatial integration and, while 11 they respond strongly to moving oriented edges, they do not show the other 12 characteristics of simple cells described above. One important property of complex cells 13 is their spatial phase invariance; i.e., strong responses are evoked by oriented gratings 14 with the preferred orientation, but for a wide range of spatial phases.…”
mentioning
confidence: 90%